MiR-378a-5p Regulates Proliferation and Migration in Vascular Smooth Muscle Cell by Targeting CDK1 - Liu, Shaoyan; Yang, Yanyan; Jiang, Shaoyan; Xu, Hong; Tang, Ningning; Lobo, Amara; Zhang, Rui; Liu, Song; Yu, Tao; Xin, Hui (Frontiers in Genetics, 2019)
Objective: Abnormal proliferation or migration of vascular smooth muscle cells (VSMCs) can lead to vessel lesions, resulting in atherosclerosis and in stent-restenosis (IRS). The purpose of our study was to establish the role of miR-378a-5p and its targets in regulating VSMCs function and IRS. Methods: EdU assays and Cell Counting Kit-8 (CCK-8) assays were applied to evaluate VSMCs proliferation, wound healing assays and transwell assays were applied to assess cells migration. Furthermore, quantitative reverse transcription–polymerase chain reaction (qRT-PCR) was performed to investigate the expression level of miR-378a-5p in stent-restenosis patients and healthy individuals. Target genes were predicted using TargetScan and miRanda software, and biological functions of candidate genes were explored through bioinformatics analysis. Moreover, RNA-binding protein immunoprecipitation (RIP) was carried out to analyze the miRNAs interactions with proteins. We also used Immunofluorescence (IF) and fluorescence microscopy to determine the binding properties, localization and expression of miR-378a-5p with downstream target CDK1. Results: The expression of miR-378a-5p was increased in the group with stent restenosis compared with healthy people, as well as in the group which VSMCs stimulated by platelet-derived growth factor-BB (PDGF-BB) compared with NCs. MiR-378a-5p over-expression had significantly promoted proliferative and migratory effects, while miR-378a-5p inhibitor suppressed VSMC proliferation and migration. CDK1 was proved to be the functional target of miR-378a-5p in VSMCs. Encouragingly, the expression of miR-378a-5p was increased in patients with stent restenosis compared with healthy people, as well as in PDGF-BB-stimulated VSMCs compared with control cells. Furthermore, co-transfection experiments demonstrated that miR-378a-5p over-expression promoted proliferation and migration of VSMCs specifically by reducing CDK1 gene expression levels. Conclusions: In this investigatory, we concluded that miR-378a-5p is a critical mediator in regulating VSMC proliferation and migration by targeting CDK1/p21 signaling pathway. Thereby, interventions aimed at miR-378a-5p may be of therapeutic application in the prevention and treatment of stent restenosis.